2008
DOI: 10.2528/pierc08012306
|View full text |Cite
|
Sign up to set email alerts
|

Broadb and High-Gain E-Shaped Microstrip Antennas for High-Speed Wireless Networks

Abstract: New electromagnetically coupling fed low profile broadband high gain E-shaped microstrip antennas (MSA) were proposed for high speed wireless networks in IEEE 802.11 a and j standards. The proposed antenna uses an E-shaped microstrip patch covered by a radome and fed by an electromagnetically coupled strip. To validate this concept, a single antenna element and a sub-array were designed, built and measured. The measured results indicate that the element and the sub-array cover the band from 4.8 to 6.0 GHz (ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…As shown in the figure, the maximum achievable peak gain is 9.5 dBi at the frequency of 2.06 GHz and the gain is better compare to design reported in [5][6][7][8][9][10][11][12][13][14][15]. In addition, the design in [10] is based on foam substrate that is more complex than our design which is based on air substrate.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…As shown in the figure, the maximum achievable peak gain is 9.5 dBi at the frequency of 2.06 GHz and the gain is better compare to design reported in [5][6][7][8][9][10][11][12][13][14][15]. In addition, the design in [10] is based on foam substrate that is more complex than our design which is based on air substrate.…”
Section: Resultsmentioning
confidence: 78%
“…A better gain of 9.5 dBi is achieved compared to the design reported in [4][5][6][7][8][9][10][11][12][13][14][15]. Figure 1 depicts the geometry of the LEE-H patch antenna.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Generally the thickness of substrate is less than one-tenth of the wavelength λ 0 . Meanwhile, the dielectric constant ε r of the substrate plays the same role in increasing edge field and its radiation power [21,22]. The configuration parameters of the patch antenna as is shown in Fig.…”
Section: Configuration Of Cylindrical Microstrip Antennasmentioning
confidence: 99%
“…Denidni and N. Hassaine [12] reported that antenna operates at the frequency band from 4.8GHz to 6.0GHz. M.R.…”
Section: Literature Reviewmentioning
confidence: 99%